Effect of aging temperature on energy dissipation and high-cycle fatigue properties of FV520B stainless steel. (1st February 2021) - Yang, Wenping; Guo, Qiang; Fan, Junling; Guo, Xinglin; Zhao, Yanguang
Highlights: Effect of ageing temperature on energy dissipation of FV520B. Infrared thermography methodology and microstructure analysis. Energy dissipation estimation considering natural and forced convections. Abstract: The aging temperature has a great influence on the microstructure of FV520B martensitic precipitation hardened stainless steel. In this work, an estimation method of energy dissipation considering convection (including natural and forced convections) and radiation heat transfer is improved. With this method, the change rules of FV520B energy dissipation under fatigue loadings after different aging treatments were studied. The relationship between FV520B energy dissipation and microstructure and fatigue fracture was analysed. It is found that, with the increase of aging temperature, the microstructure of the material tends to be uniform, and the toughness increases, while the strength decreases; the energy dissipation under cyclic loading increases with the aging temperature, which may be closely related to the microstructure of the material; the fatigue property of the material becomes worse as the aging temperature increases. Infrared thermography can greatly shorten the design and development processes for new materials.